2015
DOI: 10.1111/jog.12669
|View full text |Cite
|
Sign up to set email alerts
|

Case of early postoperative adhesion in a patient with molimina due to transverse vaginal septum concomitant with imperforate hymen

Abstract: Transverse vaginal septum is a residual vaginal plate composed of the Müllerian duct and urogenital sinus. Imperforate hymen results from failure of perforation of the membrane between the urogenital sinus and vaginal cavity. We report a rare case of concurrence of these two conditions. A 16-year-old girl had been treated with puncture several times for hematometra and hematocolpos from 13 years of age because of monthly occurrence of lower abdominal pain without menstrual bleeding and was referred to our hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…To date, the simultaneous occurrence of these two congenital anomalies has rarely been reported. [2][3][4] The present case is the first in the literature to show that the coexistence of imperforate hymen and transverse vaginal septum can be one of the benign conditions resulting in increased levels of CA-19-9, CA-125 and CEA. Although tumour markers are not routinely required for diagnosis, it has been reported that patients with CVO in premenarcheal age might exhibit increased CA-125 and C-19-9 levels (Table 2), [7][8][9][10][11][12][13][14] but CEA was not measured.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…To date, the simultaneous occurrence of these two congenital anomalies has rarely been reported. [2][3][4] The present case is the first in the literature to show that the coexistence of imperforate hymen and transverse vaginal septum can be one of the benign conditions resulting in increased levels of CA-19-9, CA-125 and CEA. Although tumour markers are not routinely required for diagnosis, it has been reported that patients with CVO in premenarcheal age might exhibit increased CA-125 and C-19-9 levels (Table 2), [7][8][9][10][11][12][13][14] but CEA was not measured.…”
Section: Discussionmentioning
confidence: 64%
“…Various aetiologies of congenital vaginal obstruction (CVO) have been well documented, including imperforated hymen, vaginal atresia and transverse vaginal septum, 1 but the reported cases with lesions occurring in combination are scarce. 2 4 Because patients with CVO are usually asymptomatic in childhood, the delayed diagnosis is often made in the setting of primary amenorrhoea and/or compression symptoms relating to the haematocolpometra. 1 This current case report describes a rare and instructive case with the coexistence of imperforate hymen and transverse vaginal septum.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients described in case reports, there were five patients with transverse vaginal septum combined with imperforate hymen [22,23,24,25,26] and one patient with uterocervicovaginal septum [27]. Also, there was one patient who was a neonate at the time of diagnosis with sacral agenesis [3] not fully separated with an imperforate hymen.…”
Section: Discussionmentioning
confidence: 99%
“…However, symptom recurrence due to vaginal adhesions is possible. In such a condition, silicon dilators can be used following re-resection ( 6 ) . Women with uterus didelphys have a high likelihood of becoming pregnant, with approximately 80% of patients able to conceive, but with elevated rates of premature delivery (22%) and abortion (74%); cesarean section is necessary in over 80% of patients ( 7 ) .…”
Section: Discussionmentioning
confidence: 99%